History, Myth and Utopia: Myth Poetics Identities in Chilean Poetry [Historia, Mito y Utopía: Identidades Mitopoéticas en la Poesía Chilena] - Nomez-Diaz, N (Universitat Autonoma de Barcelona, 2019)
Myth appears in the beginning of human life as narration or fiction, as explanation of the natural order or as mitopoiesis or consciousness creation, from where literature takes out its subject matter in order to create a kind of “private” mythology. From here, this work explores the critical reformulation of original myths in relation to Latin American and Chilean history and its heroic and degraded, utopic and distopic, real or symbolic re-foundation. From the mythical-historical rewriting of poets Pablo Neruda and Pablo de Rokha, representations of mythopoetic identities done for other Chilean poets of the XX century, like Nicanor Parra, Enrique Lihn, Jorge Teillier, Efraín Barquero, Gonzalo Millán, Raúl Zurita, and Elvira Hernández are briefly analized. © 2019 Universitat Autonoma de Barcelona. All rights reserved.